Characterization of patients with cerebrovascular diseases in the acute stage according to traditional Chinese diagnosis - Omar Morejón Barroso; Zaida Pérez Meneses; Ernesto Julio Bernal Valladares; Leticia Varela Castro (Medisur)
Foundation: In Chinese medicine, strokes are related to wind stroke syndrome (Zhong Feng), which corresponds in Western medicine to hemorrhagic and ischemic strokes. Objective: to characterize patients with strokes in the acute stage according to Chinese medicine diagnosis. Methods: descriptive case series study (n=40), which included patients treated from March to December 2018 at the Dr. Gustavo Aldereguía Lima Hospital, Cienfuegos. The analyzed variables were: age, sex, type of cerebrovascular disease in the acute stage, severity of the wind stroke attack, syndrome according to organs and viscera, and pathogenic factor present. Results: thrombotic strokes predominated, of which 75.0% behaved as severe flaccid type wind stroke; and 81.3% were associated with liver blood failure syndrome. Embolics: mild attacks in 33.3%; and 18.8% liver blood failure syndrome. Intraparenchymal cerebral hemorrhages: 62.5% severe tense attack; and 71.4% liver fire. Subarachnoid hemorrhage: 15% as severe flaccid type attack; and 17.6% liver Yin deficiency syndrome. The most frequent pathogenic factor was internal wind, present in 90.0% of cases. Conclusions: the analysis of patients with stroke in the acute phase according to traditional Chinese diagnosis showed that there is a clinical relationship with wind stroke syndrome and the Zhang fu of Chinese medicine.